Toksisitas Akut Ektrak N-Heksan Dan Methanol Rimpang Jeringau Merah Terhadap Kematian Artemia Salina Leach Dengan Metode Brine Shrimp Lethality Test - Edy Suwandi; Supriyanto Supriyanto (Jurnal Laboratorium Khatulistiwa, 2018)
Abstract: Acorus sp (red sweet flag) is an endemic plant from West Borneo which contains chemical substances such as flavonoids that have bioactivity as antioxidants so it is recommended one to prevent cancer. The study aimed to determine toxicity of n-Hexan extract and methanol red sweet flag rhizomes against Artemia salina Leach with Brine Shrimp Lethality Test method. This study was a type of quasi experimental design, sampling technique obtained by using purposive sampling. According to the study results, it can be seen than methanol extract from red sweet flag rhizomes give impact on the mortality average of Artemia salina Leach : concentration 100 µg/ml (51%), 250 µg/ml (75%), 500 µg/ml (92%), 750 µg/ml (96%) and 1000 µg/ml (99%). In addition, n-Hexan extract of red sweet flag rhizomes in 100 µg/ml (45%), 250 µg/ml (60%), 500 µg/ml (92%), 750 µg/ml (84%) and 1000 µg/ml (96%). It is reported based on probit analysis that LC50 of n-Hexan extract from red sweet flag rhizomes was 128.2921 µg/ml meanwhile methanol extract was 242.7169 µg/ml µg/ ml, thus in conclusion n-Hexan and methanol extract of red sweet flag rhizomes potentially cytotoxic to Artemia salina Leach larvae.Abstrak: Jeringau merah (Acorus sp) merupakan satu jenis tanaman endemik Kalimantan Barat memiliki kandungan kimia diantaranya flavonoidyang mempunyai bioaktivitas sebagai antioksidan sehingga sangat baik untuk pencegahan kanker. Penelitian ini bertujuan mengetahui mengetahui dan menentukan toksisitas ekstrak n-Heksan dan Methanol Rimpang Jeringau MerahterhadapArtemia salinaLeachdengan metode Brine Shrimp Lethality Test. Desain penelitian ini adalah eksperimental semu, teknik pengambilan sampel dengan cara purposive sampling. Berdasarkan hasil penelitian diketahui ekstrak Methanol Rimpang Jeringau Merah rerata kematianArtemia salina Leach konsentrasi 100 µg/ml (51%), 250 µg/ ml (75%), 500 µg/ml (92%), 750 µg/ml (96%) dan 1000 µg/ml (99%)pada ekstrak n-Heksan Rimpang Jeringau Merah konsentrasi 100 µg/ml (45%), 250 µg/ml (60%), 500 µg/ml (92%), 750 µg/ml (84%) dan 1000 µg/ml (96%). Dari analisis probit diketahuinilai LC50 ekstrak n-Heksan Rimpang Jeringau Merah yaitu 128.2921 µg/ml dan ekstrak Methanol Rimpang Jeringau Merah yaitu 242.7169 µg/ml µg/ml, maka disimpulkan ekstrak n-Heksan dan Methanol Rimpang Jeringau Merahbersifat sitotoksik terhadap larva Artemia salina Leach.